A New Routing Algorithm for Hierarchical Wireless Sensor Networks - Rana Hussain (University of Thi-Qar Journal of Science, 2019)
Wireless sensor networks (WSNs) have become an interesting area to researchers in recent years due to the lowcost of sensor nodes, wide application areas and with low or no cost of maintenance after deployment in a target area. Insome sensor system applications, the nodes are hard to reach and it is impossible to replace their batteries. So the nodesmust operate without battery replacement for a long time. Such conditions make the system power consumption a verycrucial parameter. Thus, Clustering is an energy efficient way that divides sensor nodes into many clusters, each ofwhich has a cluster head. In this paper a new cluster-based routing algorithm for hierarchical WSNs has been proposedto select an alternative node to get replaced in place of node which loses its energy such that it extends the lifetime ofentire network and avoids data loss. The simulation results show that, for large scale WSNs, our proposed algorithmperforms better than the typical existing routing algorithms in terms of network lifetime